Detachment of the Klaipėda Region from Lithuania in 1939 – a catalyst for the Second World War? (Part 2) - Vyšniauskas Аrūnas (Genocidas ir rezistencija, 2025)
Continuing the investigation begun in the first part of the article published in issue No 57 of Genocidas ir rezistencija, this second part focuses on the beginning of Great Britain’s ‘Stop Hitler’ policy in the latter half of March 1939, emphasising efforts to expand the international anti-Hitler coalition. This part of the article reveals that the acceleration of the formation of Hitler’s pre-war stopping coalition in Europe synchronously coincided with the situation regarding the Klaipėda (Memel) region that captured the world’s attention for several days in the last decade of March 1939 (especially the week of March 20–26). The English‑language press of the time portrayed these events as interconnected. The article underscores Poland’s particular stance on joining the ‘Stop Hitler’ coalition, linking it to Warsaw’s nervous reaction to the detachment of the Klaipėda Region from Lithuania. Analysis of Western English‑language press shows that German propaganda had failed to persuade foreign audiences that the Lithuanian government had voluntarily ceded the Klaipėda Region, supposedly choosing to rid itself of unnecessary territorial ballast, as though this had occurred without Germany threatening to use force against its small neighbour. The article also presents factual material reflecting the U.S. Department of State’s position, which did not recognise the legality of the Klaipėda Region’s absorption into the German Reich. It is noted that by the end of March 1939, insightful analytical assessments had begun to appear in the American media predicting that the destruction of Czechoslovakia and Germany’s annexation of the Klaipėda Region were only a prelude to further eastward expansion by Hitler and an eventual clash with the Western democracies. This is precisely what happened, ultimately leading to the outbreak of World War II. Certain issues relevant for further research are singled out – particularly those concerning the genesis of the Molotov–Ribbentrop Pact and other origins of World War II.